Overpaid Clerks, Underpaid Managers: Estimates of Public-Private Sector Wage Gap in the Philippines - Olfindo, Rosechin (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2018)
Public sector employment is often viewed as a good job—well-paid and secure. Most studies fnd that public sector employees enjoy a wage premium over their private sector counterparts. Using data from the Philippines, this article diferentiates employees into managers and administrative employees, and fnds that the public sector wage premium is largest among administrative workers in the highest pay scale, followed by managers in the middle pay scale. The estimates are derived using the most common techniques in the literature. While the magnitude of the wage premium varies depending on the method used, the order of who benefts the most from public sector employment remains consistent across methodologies. These fndings imply that managers are likely to leave the public sector after they have reached the middle pay scale, while the administrative employees are likely to remain longer to reach the highest pay scale and enjoy the largest wage premium.